EFFECTIVENESS OF STRENGTHENING CASES OF METALLIC CYLINDRICAL TANKS BY FRP REINFORCEMENT BASED ON FIBERS OF DIFFERENT TYPES (Collection of scientific works «Modern structures of metal and wood», 2024)
The park of metal cylindrical tanks in Ukraine is characterized by significant wear of load-bearing structures, corrosion of elements and metal fatigue of vertical connections. One of the solutions to the replenishment of the lost load-bearing capacity of their walls is the reinforcement by external transverse FRP. It is also make it possible to ensure tightness and anti-corrosion protection of these constructions. At the same time, existing recommendations assessing the effective use of various types of FRP, differing in strength, deformation and thermal deformation parameters, are insufficient in relation to the strengthening of metal cylindrical shells. This work systematizes systematize the method of practical determination of the parameters of the stressed state of elements of metal cylindrical shells reinforced with external transversely directed FRP reinforcement and detecting the main factors influencing the effectiveness of the use of FRP based on fibers of various types in combination with steels of different strengths. The  analysis  of  the  given  theoretical  dependencies  allows  to  conclude  that  the  mandatory factors  to  be  taken  into  account  for  strengthening  of  the  metal  cylindrical  shells  by  external transversely directed FRP reinforcement that perceives the actions of ring forces are the temperature deformations of used FRP materials, as well as the longitudinal deformations of the metal components of complex walls.  The  main  factors  determining  the  effectiveness  of  the  obtained  solutions  are  the  residual strength  of  the  material  of  the  metal  shells  and  the  modulus  of  elasticity  of  the  used  FRP.  The influence  of  thermal  deformations  can  repeatedly  change  the  required  degree  of  external reinforcement of structures in the case of the using FRP based on various types of structural fibers in combination with steel shells that characterized by low material strength, while similar combinations with high-strength steels can neutralize the influence of temperatures.  The effective use of low-modulus FRP can be achieved for reinforcements of the structures with  high  strength  characteristics  of  steel.  For  the  structures  characterized  by  low  steel  strength effective external reinforcement is achieved in combination with high-modulus FRP. The influence of temperature deformations leads to that the FRP reinforcements made on the basis of aramid fibers demonstrate relative ineffectiveness in combination with shells characterized by low steel strength.